Analisis Peran Strategis Kepemimpinan Kepala Sekolah terhadap Efektivitas Kolaborasi Sekolah-Komunitas - Aisyah Fahriyah; Aghisna Ilma; Ciha Nathania Nayoan; Maisya Laily Azmi; Noor Azizah; Zaskia Fauzia Hayaty; Suhaimi Suhaimi (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to explore the crucial role of principal leadership in optimizing the effectiveness of collaboration between educational institutions and the community. This study applies a qualitative approach through a literature study method by analyzing various academic sources related to principal leadership and educational synergy. The reviewed literature was collected through exploration in various academic repositories using search terms relevant to the scope of the analysis. Based on the literature selection process, this study analyzed 17 scientific articles related to the focus of the study. The data were analyzed qualitatively through stages of data reduction, thematic grouping, and synthesis of findings. The results of the analysis show that principal leadership plays a strategic role in strengthening the effectiveness of school–community collaboration. The effectiveness of partnerships is influenced by the principal’s ability to build open communication, encourage community participation, develop innovations in partnership activities, and build trust between educational institutions and other stakeholders. Collaborative and participatory leadership strengthens the synergy between schools and communities, thereby supporting sustainable improvement in the quality of education.